2019
DOI: 10.3390/fluids4020088
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Optimization of a Stall Margin Enhancing Recirculation Channel for an Axial Compressor

Abstract: A proof of concept is provided by computational fluid dynamic simulations of a new recirculating type casing treatment. This treatment aims at extending the stable operating range of highly loaded axial compressors, so to improve the safety of sorties of high-speed, high-performance aircraft powered by high specific thrust engines. This casing treatment, featuring an axisymmetric recirculation channel, is evaluated on the NASA rotor 37 test case by steady and unsteady Reynolds Averaged Navier Stokes (RANS) sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Preliminary work of Kawase and Rona [23] in this area confirms that the use of recirculation channels reduces losses in the blade tip area and has a positive effect on compressor stability. This is done mainly by mitigating the flow leakage between the concave and convex sides of the airfoil.…”
Section: Compressor Researchmentioning
confidence: 83%
“…Preliminary work of Kawase and Rona [23] in this area confirms that the use of recirculation channels reduces losses in the blade tip area and has a positive effect on compressor stability. This is done mainly by mitigating the flow leakage between the concave and convex sides of the airfoil.…”
Section: Compressor Researchmentioning
confidence: 83%
“…Rotational speed [r/min Modern compressors of gas turbine engines, utilized in aircraft or other applications, are regularly developed to increase their efficiency and to achieve higher total pressure ratios with less degradation of their performance 1 . This is usually accompanied by increasing the stage loading which causes the engine weight and length to decrease 2 .…”
Section: List Of Symbolsmentioning
confidence: 99%
“…They reported that TLV delaying the deterioration of the tip flow field and increased rotor performance. Kawase and Aldo [20] used recirculation channel to enhance the stall margin of axial compressor. The results demonstrated that 18.2 % axial position of fluid improve the stall margin by 5.5%.…”
mentioning
confidence: 99%